A irracionalidade e transcendência dos números - Mascarenhas, Sebastião Pontes (2017)
This present work is an explanation orientated for the check of the irracionality of some real numbers, for the construction of some transcendents numbers (in especial, the Liouville´s numbers) and for the transcendency of e, π and anothers numbers. The understanding of the presents demonstrations in this work involves some basics knowledge in theory of numbers (divisibility, highest divisor common, number prime, etc), theory of conjunct (enumerate), Differential and Integral Calculation in a real variable, a few of functions of two variables e some facts about convergence of sequences and series. As a consequence, will be seen the solution of the old problem of the quadrature of a circle, that is, a possibility ou not of the construction with ruler and compass of a square, whose area be equal to area of a circle radius gived.